Difficulties that Oman's school principals see as being faced by teachers - Al Busaidi, Ibrahim Ahmed Salem (Journal of Educational and Psychological Sciences, 2018)
The objective of this study was to identify the administrative and technical difficulties faced by principals and their principals in the Sultanate of Oman by the faculty. To achieve the objectives of the study, the analytical descriptive method was used. A questionnaire was constructed consisting of two axes: administrative difficulties, 44 paragraphs, technical difficulties,, And the sample of the study consisted of 214 managers and managers who were randomly chosen. The results of the study indicated that the administrative difficulties on the average of (2.84) with (intermediate) grade, while the technical difficulties got an average of (3,00) The importance of diversifying training courses for Irrigation schools, and activating the efficiency of annual reports for teachers, holding regular meetings of school principals to discuss the difficulties they face.
Keywords: difficulties; school principals and principals; teaching staff